1984
DOI: 10.1002/j.1460-2075.1984.tb02154.x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of an ochre suppressor tRNA gene and expression in mammalian cells.

Abstract: We have used site‐specific mutagenesis to change the anticodon of a Xenopus laevis tyrosine tRNA gene so that it would recognize ochre codons. This tRNA gene is expressed when amplified in monkey cells as part of a SV40 recombinant and efficiently suppresses termination at both the ochre codon separating the adenovirus 2 hexon gene from a 23‐kd downstream gene and the ochre codon at the end of the NS1 gene of influenza virus A/Tex/1/68. Termination at an amber codon of a NS1 gene of another influenza virus str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
36
1

Year Published

1985
1985
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 34 publications
2
36
1
Order By: Relevance
“…By using site-specific mutagenesis, Su' tRNA genes functional in mammalian cells have been generated. These include amber and ochre Su' tRNA genes derived from a Xenopus laevis tRNATYr gene (18,19) and amber, ochre, and opal Su' tRNA genes derived from a human tRNASer gene (4). In addition, cell lines carrying the X. laevis amber Su' tRNATYr gene and human amber Su' tRNAser gene have been established (15, 32a).…”
mentioning
confidence: 99%
“…By using site-specific mutagenesis, Su' tRNA genes functional in mammalian cells have been generated. These include amber and ochre Su' tRNA genes derived from a Xenopus laevis tRNATYr gene (18,19) and amber, ochre, and opal Su' tRNA genes derived from a human tRNASer gene (4). In addition, cell lines carrying the X. laevis amber Su' tRNATYr gene and human amber Su' tRNAser gene have been established (15, 32a).…”
mentioning
confidence: 99%
“…The availability of a wide variety of nonsense suppressor tRNA genes has played a crucial role in the isolation and study of nonsense mutations in procaryotes and lower eucaryotes (7). In mammalian cells, it has so far not been possible to isolate cell lines carrying nonsense suppressors by using classic genetic selections; consequently, nonsense mutations have been identified in only a few nonviral genes (8,21).Recently, we demonstrated that both a Xenopus laevis tRNATYr gene and a human tRNAser gene could be altered by oligonucleotide-directed site-specific mutagenesis to recognize and suppress amber (UAG) and ochre (UAA) codons in vivo (5,19,20). An opal (UGA) suppressor tRNA gene derived from a human tRNAser gene was also constructed (5).…”
mentioning
confidence: 99%
“…However, since the opal suppressor tRNA gene could not be propagated in mammalian cells as part of a replicating simian virus 40 (SV40) recombinant, it was not possible to demonstrate its functional expression. In addition, the X.laevis tRNATYr amber and ochre suppressors were also used to establish permanent Su' mammalian cell lines (16,19), although the level of nonsense suppression in these cell lines was low (36). It is likely that many other suppressor tRNA genes which are active in mammalian cells will be constructed and used to isolate mammalian cell lines containing functional suppressors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The mammalian suppressor cell systems used for animal virus work fall into two classes. The first consists of transient suppression systems which are usually based on engineered virus vectors [frequently simian virus 40 (SV40)] that encode the nonsense Sup + tRNA (Laski et al, , 1984Capone et al, 1985). The second category comprises various permanent cell lines in which the Sup + tRNA gene has been stably integrated into the cell genome: both constitutive and inducible systems are available (Hudziak et al, 1982;Young et al, 1983;Sedivy et al, 1987).…”
Section: Introductionmentioning
confidence: 99%